Sociodemographic and Clinical Features of Gender Identity Disorder: An Italian Multicentric Evaluation. (21st November 2012) - Fisher, Alessandra D.; Bandini, Elisa; Casale, Helen; Ferruccio, Naika; Meriggiola, Maria C.; Gualerzi, Anna; Manieri, Chiara; Jannini, Emmanuele; Mannucci, Edoardo; Monami, Matteo; Stomaci, Niceta; Delle Rose, Augusto; et al.
ABSTRACT Introduction. Male to female (MtFs) and female to male (FtMs) subjects with gender identity disorder (GID) seem to differ with regard to some sociodemographic and clinical features. Currently, no descriptive studies focusing on MtFs and FtMs attending an Italian clinic are available. Aim. To describe the sociodemographic characteristics of a GID population seeking assistance for gender transition and to assess possible differences in those features between MtFs and FtMs. Methods. A consecutive series of 198 patients was evaluated for gender dysphoria from July 2008 to May 2011 in four dedicated centers. A total of 140 subjects (mean age 32.6 ± 9.0 years old) meeting the criteria for GID, with their informed consent and without genital reassignment surgery having already been performed, were considered (92 MtFs and 48 FtMs). Diagnosis was based on formal psychiatric classification criteria. Main Outcome Measures. Medical history and sociodemographic characteristics were investigated. Subjects were asked to complete the Body Uneasiness Test (a self‐rating scale exploring different areas of body‐related psychopathology), Symptom Checklist‐90 Revised (a self‐rating scale to measure psychological state), and the Bem Sex Role Inventory (a self‐rating scale to evaluate gender role). The presence of psychiatric comorbidities was evaluated using the Structured Clinical Interviews for Diagnostic and Statistical Manual of Mental Disorders, 4th Edition, Text Revision (DSM‐IV‐TR) (SCID I and SCID II). Results. Several significant differences were found between MtFs and FtMs regarding lifestyle and sociodemographic factors and in psychometric test scores. No differences were found in terms of psychiatric comorbidity. Conclusions. This is the first large study reporting the sociodemographic characteristics of a GID sample referring to Italian clinics, and it provides different profiles for MtFs and FtMs. In particular, FtMs display significantly better social functioning. Fisher AD, Bandini E, Casale H, Ferruccio N, Meriggiola MC, Gualerzi A, Manieri C, Jannini E, Mannucci E, Monami M, Stomaci N, Delle Rose A, Susini T, Ricca V, and Maggi M. Sociodemographic and clinical features of gender identity disorder: An Italian multicentric evaluation. J Sex Med **;**:**–**.